Asset Price Bubbles : A Selective Survey - Scherbina, Anna (IMF Working Papers; Working Paper ;, 2013)
Why do asset price bubbles continue to appear in various markets? This paper provides an overview of recent literature on bubbles, with significant attention given to behavioral models and rational models with frictions. Unlike the standard rational models, the new literature is able to model the common characteristics of historical bubble episodes and offer insights for how bubbles are initiated and sustained, the reasons they burst, and why arbitrage forces do not routinely step in to squash them. The latest U.S. real estate bubble is described in the context of this literature.